Informální u č ení v karié ř e žen. / Informal learning within the career development of women. - Lenka Hloušková (Pedagogická Orientace, 2013)
The aim of this text is to describe how informal learning influences the career development of women. Answer to the above mentioned question follows from a qualitative study within a research study on the topic: The needs of adults in relation to the building of their careers and how to satisfy these through career counselling andguidance services. Qualitative approach was implemented as biographic research with the use of the life story method. For the purpose of this text, we used a sample of seven women of different ages, the same degree of education, with at least one-year-work experience and with different types of changes in their careers. The data suggest that women learn informally either due to the pressure of a situation or „for the future“. If women learn as a result of the pressure of the situation, informal learning represents a tool for satisfying needs that are perceived as deficit. In fact, these women don'tplan their career development in a long-term perspective and from the point of view of career building, informal learning becomes a tool for changing the current state. In case that women learn for the future, via learning they try to satisfy needs which canbe regarded (according to Maslow) as the self-realization needs. These women plan their career development and this is why it is possible to consider informal learning as a direct tool for their career development.